Analysis study of sensitive volume and triggering criteria of single‐event burnout in super‐junction metal‐oxide semiconductor field‐effect transistors. Issue 3 (1st May 2014) - Zerarka, Moustafa; Austin, Patrick; Morancho, Frédéric; Isoird, Karine; Arbess, Houssam; Tasselli, Josiane
Abstract : Power metal‐oxide semiconductor field effect transistors (MOSFETs) are more and more used in atmospheric and space applications. Thus, it is essential to study the influence of the natural radiation environment on the electrical behaviour of vertical double‐diffused metal‐oxide semiconductor (VDMOS) and super‐junction (SJ) MOSFETs. Two‐dimensional numerical simulations are performed to define the sensitive volume and triggering criteria of single‐event burnout (SEB) for VDMOS and SJ MOSFETs for different configurations of ionising tracks. The analysis of the results allows a better understanding of the SEB mechanism in each structure and allows the behaviour and robustness comparison for these two technologies under heavy‐ion irradiation.